Experimental study on the effect of compressor frequency on the performance of a combined trans-critical CO2 system. (25th July 2020) - Cui, Ce; Wei, Xiangyu; Song, Yulong; Yin, Xiang; Cao, Feng; Wang, Xiaolin
Highlights: Capacity ratio of the main/auxiliary compressor was experimentally investigated. Experiments dealing with variable frequencies were massively conducted. The COP was increased by 6.67% under the design condition. The performance improvement decreased with the augment of ambient temperature. Abstract: A trans-critical CO2 heat pump combined system was developed to improve the cycle performance under the working condition of low ambient temperature and high return water temperature. Large amounts of experimental investigation dealing with the variation of the frequency in the trans-critical CO2 combined system were carried out to research into the influence of capacity ratio between the main/auxiliary compressor on the system performance. The experimental results demonstrated the optimal discharge pressure for the both subsystems and that the frequency combination had a huge impact on the system performance. The 90/70 Hz frequency combination achieved the highest COP among all the tested frequency combinations in the ambient temperature of −20, −12 and 0 °C. The system COP was observed to increase by a maximum value of 6.7% under the design condition. The impact of the frequency combination on the optimal system COP would decrease with the augment of ambient temperature.